â€œTHE IMPACT OF E-WOM ON CONSUMER INTENTION TO SELECT HOLIDAY DESTINATIONâ€ (EMPIRICAL STUDY ON INSTAGRAM USERS IN MALANG) - Maulana, Razif (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims at examining the effect of Electronic word of mouth variable such as Intensity, Valence of Opinion, and Content on Consumer Intention of Instagram Users to select holiday destination in Malang City. The questionnaire has been distributed to 100 respondents who Instagram users and lived in Malang City. The sampling technique used is purposive sampling and the research instruments were tested using the Validity Test, Reliability Test, and Classical Assumption Test. This research uses Multiple Regression Analysis to analyze the data. The result of multiple regression analysis indicates that Content, Valence of Opinion, and Intensity are significantly effect on Consumer Intention. It also known that Content is the most powerful and dominant variable among all the independent variables. The results of this research can be applied in a marketing strategy for the company and interested parties to maintain and maximize Intensity, Valence of Opinion, and Content to obtain a positive effect of Electronic Word of Mouth on potential customers that can lead to a purchase decision.Keywords: Electronic Word of Mouth, Consumer Intention, Intensity, Valence of Opinion, Content